The Power of Undervalued Currency: A Methodological Comment - Malenbaum, Wilfred (Review of Economic Studies, 1938)
Journal Article The Power of Undervalued Currency Get access Wilfred Malenbaum Wilfred Malenbaum London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 5, Issue 2, February 1938, Pages 143–151, https://doi.org/10.2307/2967529 Published: 01 February 1938